Open source in libraries: Implementation of an open source ILMS at Asia e-University library - Abu Bakar, Amzari; Yusoff, Thami Munisah (2010)
Open source systems for libraries have improved significantly to gain the confidence of librarians. The main focus of the paper is to describe the selection process and criteria that led to the implementation of Koha the first open source Integrated Library Management System at the AeU Library. A study was made based on the set criteria used to compare and contrast with the more popular propriety library management systems. The paper presents the findings of the study which led to the selection of Koha, and a brief introduction to features of open source systems for libraries. The reasoning and conditions for accepting Koha are discussed. A brief account of the implementation process and related experience of the open source ILMS are given. AeU library implemented the various modules of the system: cataloging, online public access (OPAC), circulation, patron management and acquisitions. The expanding influence and acceptance of OSS in libraries is here to stay. Malaysian libraries may need to look into the credible options and benefits of utilizing open source systems and harness this development in ILS.